2016
DOI: 10.1136/sextrans-2016-052893
|View full text |Cite
|
Sign up to set email alerts
|

Very high incidence of syphilis in HIV-infected men who have sex with men in Buenos Aires city: a retrospective cohort study

Abstract: The incidence of syphilis in this cohort of men with HIV (predominantly MSM) was very high. In addition to maintaining high surveillance for early diagnosis and treatment, it is necessary to implement newer and more effective measures to prevent syphilis and other STIs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…A cohort study of 391 MSM in Rio de Janeiro, Brazil reported their prevalence of syphilis was 9.9% [153]. A retrospective study conducted among 1,150 men with HIV-infection in Buenos Aires, Argentina reported a syphilis incidence of 14.9 cases per 100 patients per year [154]. Most of the participants were MSM.…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study of 391 MSM in Rio de Janeiro, Brazil reported their prevalence of syphilis was 9.9% [153]. A retrospective study conducted among 1,150 men with HIV-infection in Buenos Aires, Argentina reported a syphilis incidence of 14.9 cases per 100 patients per year [154]. Most of the participants were MSM.…”
Section: Introductionmentioning
confidence: 99%
“…12 A large proportion of these patients have been noted to be HIV co-infected. 1 The article by Bissio et al published in this issue 3 extends these findings to Argentina, noting a high rate of incident syphilis in HIV-infected MSM residing in Buenos Aires. In this retrospective cohort study, the authors reviewed records of HIV-positive MSM attending an HIV clinic in Buenos Aires for follow-up at least twice in the period from March 2015 to February 2016.…”
mentioning
confidence: 79%
“…22 In Latin America, there was 2,6% syphilis prevalence occurred on Peru 24 , 9,9% on Brazil 25 , and 14,9 cases per 100 patients per year on Argentina. 26 On America, syphilis cases in 2013 to 2016 period were ranged from17,5 cases per 100.000 for white people, 23,1 cases per 100.000 persons for black people, and 10,9 cases per 100.000 persons for pacific Islander. 23 The different percentage obtained in other study of prevalence indeed affected by sample used in the study.…”
Section: Discussionmentioning
confidence: 99%